Hypofractionated radiotherapy recommendations for localized prostate cancer in Brazil - Palhares,Daniel Moore Freitas (2021)
SUMMARY OBJECTIVE: Several prospective randomized trials have shown that hypofractionation has the same efficacy and safety as the conventional fractionation in the treatment of localized prostate cancer. There are many benefits of hypofractionation, including a more convenient schedule for the patients and better use of resources, which is especially important in low- and middle-income countries like Brasil. Based on these data, the Brazilian Society of Radiotherapy (Sociedade Brasileira de Radioterapia) organized this consensus to guide and support the use of hypofractionated radiotherapy for localized prostate cancer in Brasil. METHODS: The relevant literature regarding moderate hypofractionation (mHypo) and ultra-hypofractionation (uHypo) was reviewed and discussed by a group of experts from public and private centers of different parts of Brasil. Several key questions concerning clinical indications, outcomes and technological requirements for hypofractionation were discussed and voted. For each question, consensus was reached if there was an agreement of at least 75% of the panel members. RESULTS: The recommendations are described in this article. CONCLUSION: This initiative will assist Brazilian radiation oncologists and medical physicists to safely treat localized prostate cancer patients with hypofractionation.